HUBUNGAN PEKERJA OUT SOURCING DENGAN PERUSAHAAN JASA DAN PEMBERI KERJA TERHADAP HAK-HAK PEKERJA - Sudahnan Sudahnan (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
Relation of Worker outsourcing in a company of like twofaced in one side have the relation work with the service firm, but other to beside work in employer company. Judicially worker outsourcing have the direct job relation with the service firm of but also have the indirect relation with the employer company, nevertheless rights accepted by worker outsourcing have to at least given by a same protection by employer company of according to order punish the legislation going into eject.